2022
DOI: 10.3390/cancers14153624
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Performance of Magnetic Resonance Image Compilation (MAGiC) Method: An Exploratory Analysis for Head and Neck Imaging

Abstract: The present exploratory study investigates the performance of a new, rapid, synthetic MRI method for diagnostic image quality assessment and measurement of relaxometry metric values in head and neck (HN) tumors and normal-appearing masseter muscle. The multi-dynamic multi-echo (MDME) sequence was used for data acquisition, followed by synthetic image reconstruction on a 3T MRI scanner for 14 patients (3 untreated and 11 treated). The MDME enables absolute quantification of physical tissue properties, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The research [17] in head and neck region proved the clinical feasibility of generating synthetic T1WI and T2WI images from quantitative relaxometry mapping. Recently, preliminary SyMRI studies have demonstrated a potential role in evaluating prognostic factors in breast [18,19], prostate [20], bladder [21], and rectal cancer [22,23].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The research [17] in head and neck region proved the clinical feasibility of generating synthetic T1WI and T2WI images from quantitative relaxometry mapping. Recently, preliminary SyMRI studies have demonstrated a potential role in evaluating prognostic factors in breast [18,19], prostate [20], bladder [21], and rectal cancer [22,23].…”
Section: Introductionmentioning
confidence: 84%
“…The benefit of SyMRI is twofold, providing relaxometry maps in a clinically feasible time and the ability to generate different contrast images in a single acquisition [ 17 ]. Quantitative T1, T2, and PD Mean values were reported to be lower in malignant tumors vs. benign tumors [ 20 , 27 , 28 ], and in poor prognostic relevant factors tumors vs. good prognostic relevant factors [ 20 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relaxometry values estimated with MAGiC were slightly lower on comparison to MRF results mentioned above. MAGiC and MRF are two prominent new sequences for rapid MR relaxometry and the former uses a multiple-dynamic multiple-echo (MDME) sequence for data acquisition and synthetic image reconstruction, including post-processing which is different from MRF as detailed in the method section [ 59 , 60 ]. The differences in the acquisition and reconstruction approaches could be attributed to the marginal variation observed in the mean T1 and T2 values.…”
Section: Discussionmentioning
confidence: 99%